2022
DOI: 10.5194/gmd-15-3773-2022
|View full text |Cite
|
Sign up to set email alerts
|

MagmaFOAM-1.0: a modular framework for the simulation of magmatic systems

Abstract: Abstract. Numerical simulations of volcanic processes play a fundamental role in understanding the dynamics of magma storage, ascent, and eruption. The recent extraordinary progress in computer performance and improvements in numerical modeling techniques allow simulating multiphase systems in mechanical and thermodynamical disequilibrium. Nonetheless, the growing complexity of these simulations requires the development of flexible computational tools that can easily switch between sub-models and solution tech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 104 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…The volume of fluid method is adopted in OpenFOAM to resolve the position and shape of the interface separating two fluids or phases (e.g., liquid-gas). As already shown by Brogi et al (2022), we remark that the details of the numerical solver and its parameters may affect the details of the interface geometry between the contaminated and uncontaminated melts. However, convergence tests and comparison with experimental observations (Appendix C.1) have demonstrated that the fluid solver reproduces well the overall dynamics of the mingling of two liquids enhanced by a rising bubble.…”
Section: Mingling Dynamicsmentioning
confidence: 52%
See 1 more Smart Citation
“…The volume of fluid method is adopted in OpenFOAM to resolve the position and shape of the interface separating two fluids or phases (e.g., liquid-gas). As already shown by Brogi et al (2022), we remark that the details of the numerical solver and its parameters may affect the details of the interface geometry between the contaminated and uncontaminated melts. However, convergence tests and comparison with experimental observations (Appendix C.1) have demonstrated that the fluid solver reproduces well the overall dynamics of the mingling of two liquids enhanced by a rising bubble.…”
Section: Mingling Dynamicsmentioning
confidence: 52%
“…The mingling dynamics between a contaminated, low-viscosity, gas-rich magma pocket and the uncontaminated melt are simulated using the opensource computational fluid dynamics software OpenFOAM, which has been already tested and benchmarked on volcanological problems (Brogi et al, 2022). The numerical simulations are performed with the multiphase solver icoReactingMultiphaseInterFoam which can deal with multiple incompressible non-isothermal phases and phase change.…”
Section: Mingling Dynamicsmentioning
confidence: 99%